2014
DOI: 10.1002/pon.3475
|View full text |Cite
|
Sign up to set email alerts
|

Parenting stress as a mediator of parents' negative mood state and behavior problems in children with newly diagnosed cancer

Abstract: This is the first study to demonstrate the mediational role of parenting stress in fathers of a child with newly diagnosed cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…With variation across HRQL subscales, the subset of patients with lower HRQL came from families whose parents reported higher levels of distress, and more familial risk factors, such as poor general family functioning and lack of social support. These findings support previous studies demonstrating parental distress and family risk as major factors negatively impacting patient HRQL .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With variation across HRQL subscales, the subset of patients with lower HRQL came from families whose parents reported higher levels of distress, and more familial risk factors, such as poor general family functioning and lack of social support. These findings support previous studies demonstrating parental distress and family risk as major factors negatively impacting patient HRQL .…”
Section: Discussionsupporting
confidence: 92%
“…Using the Psychosocial Assessment Tool (PAT), a measure of family risks and resources, a majority of families of children with cancer demonstrated resilience but a subset of families experienced difficulties in adaptation . These at‐risk families are more likely to exhibit increased distress over time , require more psychosocial services throughout cancer treatment and exhibit negative psychosocial outcomes for the child with cancer and the parents . In another study, family variables (family roles and parent–child relationships) were found to be associated with parent‐proxy report of patient HRQL, with better family functioning and higher parental overprotection associated with higher HRQL .…”
Section: Introductionmentioning
confidence: 99%
“…Being diagnosed with this life-threating condition imposes a lot of stress on the sufferers and their families, parent may interfere with the parent-child relationship and communication (Steele et al, 2004). Van der Geest et al, (2014) stated that changing dynamic between parent and child during initial treatment under the influence of parenting stress can affect their ability to parent their child in this stressful situation. Except anxiety and depression, parenting a child with cancer can also lead to higher levels of parenting stress (Kazak et al, 1997;Colletti et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Next to this, a consistent link has been found between low levels of child adaptation response immediately after diagnosis and later adjustment [ 14 , 15 ]. At last, parental psychosocial factors, including distress [ 16 ], low social support [ 17 ], helpless cognitions [ 18 ], avoidant/passive coping [ 19 ], and parenting stress [ 20 , 21 ] were consistently found to be risk factors for child maladjustment.…”
Section: Introductionmentioning
confidence: 99%